The impact of the oil price in the energy transition towards renewable energy consumption: dynamic panel threshold analysis - Tee, Wu Shun; Lee, Hui Shan; Lee, Chin; Law, Siong Hook (Springer Nature, 2026)
The oil consumption is important in shaping countries’ development, but the shift toward renewable energy is the current global trend in pursuit of the sustainable development goals. The volatility of oil prices raises important questions about their role in influencing renewable energy adoption. Using the dynamic panel threshold model, this study investigates the impact of oil prices on renewable energy consumption across 160 countries over the period 1995–2018, grouped by different income levels. The results for the overall sample show that oil prices above the threshold have a significant negative effect on renewable energy consumption growth. For the high-income group, high oil prices also show a statistically significant negative impact on renewable energy growth. In the upper-middle-income group, oil prices positively and significantly drive renewable energy consumption growth when below the threshold. The results imply that renewable energy consumption is highly susceptible to oil price fluctuations, creating hesitation for investors and postponing long-term commitments to clean energy projects. The novelty of this study shows the different impacts of renewable energy consumption subject to the oil price threshold. The findings of this study recommend the necessity of stable regulatory frameworks to control the uncertainty caused by oil price volatility to move towards renewable energy consumption that is environmentally friendly.